2022
DOI: 10.3389/fpsyg.2021.812490
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Enterprise Social Media on Employee Creativity: Social Exchange Theory Perspective

Abstract: This study applied an artifact-centric view to investigate the consequences of enterprise social media usage. It investigates how enterprise social media usage influences employee creativity. A moderated mediation model is developed based on social exchange theory. The empirical sample of 238 employees is used to test the proposed model. Results of the empirical analysis performed using PROCESS macro of SPSS indicate that enterprise social media usage positively impacts employee creativity via the mediating me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 54 publications
0
11
0
Order By: Relevance
“…From an institutional perspective, CIF utilizes information systems as a communication medium to expand the network of partnerships by providing information on sustainable activities. Wang et al (2022) showed that activity information published online through social company websites results from employee innovation and creativity. On the other hand, Choi et al (2020) show that employees of social enterprises with organizational commitments can give birth to new ideas in communication media innovation to bring sponsors and expand cooperation networks with other institutions.…”
Section: Resultsmentioning
confidence: 99%
“…From an institutional perspective, CIF utilizes information systems as a communication medium to expand the network of partnerships by providing information on sustainable activities. Wang et al (2022) showed that activity information published online through social company websites results from employee innovation and creativity. On the other hand, Choi et al (2020) show that employees of social enterprises with organizational commitments can give birth to new ideas in communication media innovation to bring sponsors and expand cooperation networks with other institutions.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, studies on the impact on employees’ innovativeness have been added. Wang et al [ 93 ], based on social exchange theory, found that this behavior positively affects employees’ creativity through leadership member exchange. Cheng et al [ 94 ] found that this behavior increased work engagement and thus positively influenced employees’ innovation performance.…”
Section: Discussionmentioning
confidence: 99%
“…Cai et al [ 101 ] found that this behavior enhances employees’ interpersonal relationships and thus positively affects their performance. Employees’ use of social media increased leader–member communication, which stimulated employee creativity [ 93 ]. In addition, new mediating variables have been added to the literature in the last three years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, based on the social exchange theory and the resource conservation theory, the present study hypothesizes that narcissistic leadership has a significant negative impact on employees’ job embeddedness for the following reasons. On the one hand, social exchange theory states that when employees receive moral encouragement and material help from their leaders, they will reward the leader and the organization by putting in work or supporting the leaders and a series of beneficial activities for the organization out of reciprocity ( Cropanzano et al, 2017 ; Wang Z. et al, 2021 ). Conversely, when leaders are arrogant, sensitive, angry, or lacking in empathy toward employees, employees perceive that the exchange relationship is unbalanced or that they are being used, resulting in behavioral outcomes that are detrimental to the organization, such as increased emotional exhaustion and reduced organizational commitment and embeddedness ( Glad, 2002 ).…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%